INTERFERENCES IN PRIMARY CARE FOR PUERPERAL WOMEN IN A BORDER REGION DURING THE COVID-19 PANDEMIC - Novakowiski, Rosenilda Duartes Fernandes; Contiero, Ana Paula; Backes, Marli Terezinha Stein; Zilly, Adriana; Baggio, Maria Aparecida (Cogitare Enfermagem, 2024)
Objective: To identify factors that have interfered with puerperal care in a border region during the COVID-19 pandemic. Method: qualitative research, using Grounded Theory as a methodological reference. It was developed in primary care in the triple border region of Brazil, Argentina, and Paraguay, with 30 participants, including puerperal women, health professionals, and managers. According to the Straussian perspective, data collection and analysis were collected between August 2021 and May 2022, following the stages of open, axial, and selective coding. Results: four subcategories were identified: "accessing health units", "understanding home visits and active search", "having insufficient information sharing in the care network" and "showing an overloaded health system". Conclusion: it was found that most of the factors that interfered with puerperal women’s care already existed and were aggravated by the pandemic. It is recommended that measures be put in place to guarantee the sharing of information and timely counter-referrals.